2018
DOI: 10.1002/jbt.22208
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxic and antiproliferative effects of usnic acid on hormone‐dependent breast and prostate cancer cells

Abstract: The aim of the current study was first to investigate cytotoxic activity of usnic acid (UA) on hormone-dependent breast and prostate cancer, and normal cells. Cells were treated with increasing concentrations (25 to 150 µM) of UA for 48 hours and cell viability, quantitative and morphological analysis of cell death, and cell cycle analysis were performed. UA was shown to have selective cytotoxicity on hormone-dependent cancer cells with the IC levels of 71.4 and 77.5 µM for MCF7 and LNCaP cells, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
3
15
0
Order By: Relevance
“…Furthermore, some of the most effective cancer chemotherapeutic agents (dophyllotoxin, etoposide, teniposide, vinblastine, vincristine, and taxol) to date are natural products or compounds . In our previous study, we found that UA exerted a notable anticancer effect on MCF7 and LNCaP cells without damaging control cells . However, to the best of our knowledge, the combined effects of UA and Tam or Enz have remained to be elucidated in BC and PC.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Furthermore, some of the most effective cancer chemotherapeutic agents (dophyllotoxin, etoposide, teniposide, vinblastine, vincristine, and taxol) to date are natural products or compounds . In our previous study, we found that UA exerted a notable anticancer effect on MCF7 and LNCaP cells without damaging control cells . However, to the best of our knowledge, the combined effects of UA and Tam or Enz have remained to be elucidated in BC and PC.…”
Section: Discussionmentioning
confidence: 97%
“…Stock solution of 0.1 g (+)‐UA in 20 mL DMSO was prepared and stored in the dark with appropriate temperature until used in cell culture at concentrations of 12.5 and 25 μM by diluting with each cell's own medium as previously described . Tam was prepared as 10 mM stock solution in 95% ethanol and stored at +4°C.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations